Nutritional status and its associated factors of elderly population living in old age homes of Kathmandu Metropolitan City - Bhatta, Bal Krishna; Karki, Manisha; Dahal, Maginsh; Pokhrel, Basanta (Nepal Medical College Journal, 2023)
Nutrition plays an important role in the overall well- being of human beings more so in the elderly. Elderly living at old age homes have a different nutritional status as compared to those living with their families. Thus, this study was conducted to assess the nutritional status of the elderly living in old age homes of Kathmandu Metropolitan City (KMC). A descriptive cross-sectional study was carried among 133 elderly residing in all six old age homes of KMC by using Nepali-translated Nestle’s Mini Nutritional Assessment Tool (MNA). Further collected information was analyzed using chi square test. Regarding nutritional status, 30.8% of the participants had normal nutritional status, whereas 52.7% were at risk of malnutrition and 16.5% were malnourished. Lifestyle related factors such as smoking and physical activity were found to be the factors affecting the nutritional status of elderly people. Significant association was seen between nutritional status and age (p =0.001) and past occupation (p =0.021). A significant proportion of elderly people living in old age homes are at risk of malnutrit ion or are malnourished.